The complete mitochondrial genome sequence of Squalidus multimaculatus (Cypriniformes: Cyprinidae) - Yi, Seul (Mitochondrial DNA B Resour, 2017)
This study determined the complete mitogenome sequence of Squalidus multimaculatus (Cypriniformes: Cyprinidae). The mitogenome of S. multimaculatus is 16,597 bp in length, including 13 protein-coding genes, 22 transfer RNAs, 2 ribosomal RNA genes, and a non-coding control region. NCR is 925 bp in length, is located between tRNA(pro) and tRNA(phe). The overall base composition of S. multimaculatus is 27.9% for A, 18.9% for G, 25% for T, 28.2% for C, with a slight AT bias (52.9%). These results will provide the data required for phylogenetic studies of the Squalidus species.